Student experiences of service learning through a community outreach project. Issue 6 (18th August 2018) - Mey, Michelle; Werner, Amanda; de Villiers, Bridget
ABSTRACT: This article explores the challenges experienced and value derived by human resource management students at the Nelson Mandela University, South Africa from participating in a community service project. The study is descriptive and qualitative in nature, providing a thematic and narrative summary of student experiences in a community service project as presented in portfolios of evidence. The study reveals that community service projects are a valuable tool for students to experience real life, practise desired graduate attributes and other competencies nurtured in the classroom, and deepen their socio-economic awareness. For academics they provide insight into student experiences and highlights areas in which students need support, guidance, or mentoring in a service-learning project of this nature.